Summaries of Sessions Human health and biodiversity of natural resources in the Kuroshio region - Chiu-Chin, Lu; Hin-Kiu, Mok; Hurng-Wern, Huang; Chao-Neng, Tseng; Awang Ahmad Sallehin, Awang Husaini; Soo Hui, Yin; Ngieng Ngui, Sing; Azham, Zulkharnain; Lesley Maurice, Bilung; Velnetti, Linang; Micky, Vincent; Kasing, Apun; et al. (Graduate School of Kuroshio Science, Kochi University, 2014)
This session consists of eight topics. Since the following three papers are separately presented, we do not summarize them: “Spirulina Complex Polysaccharides Suppress the Growth of Glioma in TLymphocytesand Macrophage-dependent Manner” by Akira Tominaga et al., “Rapid Screening for Cytotoxicity and Group Identification of Secondary Metabolites in Methanol Extracts from Four Sponge Species Found in Kapoposang Island, Spermonde Archipelago, Indonesia” by Ajuk Sapar, and “Inventory of Medicinal Plants for Fever Used by Four Dayak Sub Ethnic in West Kalimantan Province, Indonesia” by Fathul Yusro et al.